(untitled) (Sains Humanika, 2022)
Collaboration between vocational colleges and industries is indeed significant to produce graduates who are industry relevant and ready to face future challenges. The smart partnerships between vocational colleges and industries have created a good synergy in transforming the talent of graduates which ultimately contribute to the development of the nation. This study was conducted to identify the collaboration gap between vocational colleges and the industries. The Borich evaluation model was used as an approach in achieving the main objective of this study which is to identify collaboration gap between vocational colleges and industries. Researchers used the entire population of 195 vocational academic staffs as the respondents for this study. The data of this study were obtained through questionnaires and analyzed using MWDS (Mean Weight Discrepancy Score). Six aspects of collaboration identified through literature include a) placement of staffs in the industry b) curriculum c) added value c) support d) facilities and e) training. Using the Borich needs assessment method, placement of academic staff in the industry showed the largest collaboration gap (MWDS=1.43), followed by the collaboration for facilities sharing (MWDS=1.09), collaboration in training (MWDS=0.90), collaboration in support (MWDS=0.81) and collaboration in providing added value for the students. The smallest collaboration gap is the curriculum aspect (MWDS=0.71).